2021
DOI: 10.3390/galaxies9040077
|View full text |Cite
|
Sign up to set email alerts
|

A Roadmap to Gamma-Ray Bursts: New Developments and Applications to Cosmology

Abstract: Gamma-ray bursts are the most powerful explosions in the universe and are mainly placed at very large redshifts, up to z≃9. In this short review, we first discuss gamma-ray burst classification and morphological properties. We then report the likely relations between gamma-ray bursts and other astronomical objects, such as black holes, supernovae, neutron stars, etc., discussing in detail gamma-ray burst progenitors. We classify long and short gamma-ray bursts, working out their timescales, and introduce the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 260 publications
(379 reference statements)
0
10
0
Order By: Relevance
“…Amati et al [6] showed that the ΛCDM model is statistically favoured over the wCDM scenario. Moreover, Khadka and Ratra [7] found that the cosmological parameters obtained from GRBs were consistent with baryon acoustic oscillation and Hubble parameter measurements and the GRBs could be used as complementary and outstanding probes to trace dark energy's evolution in support of other indicators [8,9].…”
Section: Introductionmentioning
confidence: 73%
“…Amati et al [6] showed that the ΛCDM model is statistically favoured over the wCDM scenario. Moreover, Khadka and Ratra [7] found that the cosmological parameters obtained from GRBs were consistent with baryon acoustic oscillation and Hubble parameter measurements and the GRBs could be used as complementary and outstanding probes to trace dark energy's evolution in support of other indicators [8,9].…”
Section: Introductionmentioning
confidence: 73%
“…Several empirical correlations using parameters of the light curves and spectra have been proposed to standardize the GRBs' luminosity. They include correlations between: (i) the GRB spectrum lag time τ lag and isotropic peak luminosity L (τ lag -L relation) [66]; (ii) the peak energy E p of the νF ν spectrum and the isotropic equivalent energy E iso (E p -E iso relation) [67]; (iii) the time variability V and isotropic peak luminosity (V-L relation) [68]; (iv) the peak energy of the νF ν spectrum and the isotropic peak luminosity (E p -L relation) [69]; (v) the minimum rise time τ RT of the light curve and isotropic peak luminosity (τ RT -L relation) [70]; (vi) the peak energy and collimation-corrected energy E γ (E p -E γ relation) [71,72]; (vii) the peak luminosity, the time at the end of the plateau emission phase τ a , and the luminosity at the end of the plateau phase L a (L-τ a -L a relation-Dainotti 3D fundamental plane) [73][74][75]; and others, e.g., [76][77][78][79][80][81][82][83].…”
Section: Gamma-ray Bursts Hubble Diagrammentioning
confidence: 99%
“…Cosmological models have been compared and cosmological parameter constraints have been determined using various observations, including cosmic microwave background (CMB) anisotropy data, [7], that probe the highredshift Universe, and lower-redshift expansion-rate observations like those we use here. These lower-redshift data sets include better-established probes such as Hubble parameter [H(z)] data that reach to redshift z ∼ 2, and baryon acoustic oscillation (BAO) and type Ia supernova (SN Ia) measurements that reach to z ∼ 2.3, [8][9][10], as well as emerging probes such as H ii starburst galaxy (H iiG) apparent magnitude data that reach to z ∼ 2.5, [11][12][13][14][15][16], quasar angular size (QSO-AS) measurements that reach to z ∼ 2.7, [17][18][19][20][21], reverberationmeasured (RM) Mg ii and C iv quasar (QSO) measurements that reach to z ∼ 3.4, [22][23][24][25][26][27][28], and gamma-ray burst (GRB) data that reach to z ∼ 8.2, [29][30][31][32][33][34][35][36][37][38][39], of which only 118 Amati-correlated (A118) GRBs, with lower intrinsic dispersion, are suitable for cosmological purposes, [37,[40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%